2013
DOI: 10.1038/jid.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Phacomatosis Pigmentokeratotica Is a “Pseudodidymosis”

Abstract: In phacomatosis pigmentokeratotica, papular nevus spilus coexists with nevus sebaceus. The disorder was thought to be a didymosis with early postzygotic recombination. In this issue, however, Groesser and co-workers provide a new concept. Both nevi originate from a single heterozygous HRAS mutation in a pluripotent progenitor cell. This new understanding has implications for other proposed examples of didymosis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The term didymosis (twin spotting) was coined by Happle to explain the concurrent presence, in the same region, of two mutant tissue areas, different from each other and from the normal surrounding tissue . A recent molecular research has provided evidence to suggest that binary genodermatoses like phacomatoses pigmentokeratotica is due to a single pleiotropic HRAS mutation where one abnormal gene can produce two or more seemingly unrelated phenotypic traits . Hence the previously proposed term didymosis aplasticopsilolipara is now considered inappropriate .…”
mentioning
confidence: 99%
“…The term didymosis (twin spotting) was coined by Happle to explain the concurrent presence, in the same region, of two mutant tissue areas, different from each other and from the normal surrounding tissue . A recent molecular research has provided evidence to suggest that binary genodermatoses like phacomatoses pigmentokeratotica is due to a single pleiotropic HRAS mutation where one abnormal gene can produce two or more seemingly unrelated phenotypic traits . Hence the previously proposed term didymosis aplasticopsilolipara is now considered inappropriate .…”
mentioning
confidence: 99%
“…This would result from the presence of two different mutant alleles (at the same gene locus or at different loci) and a subsequent post‐zygotic recombination that gives rise to two different homozygous daughter cells forming skin lesions that are either allelic (originating from the same type of cell) or non‐allelic (originating from different types of cell) . However, the concept of non‐allelic didymosis has been questioned recently as molecular research has shown that some skin disorders previously thought to result from such a genetic phenomenon may be caused by a single post‐zygotic mutation in a pluripotent progenitor cell that is present in a heterozygous state (“pseudodidymosis”) …”
mentioning
confidence: 99%
“…In our opinion, although we cannot exclude a random co‐occurrence of the two lesions, their close spatial arrangement would render a causal relationship rather likely. According to the new concept of pseudodidymosis, it is possible to speculate that these lesions may have resulted from a single post‐zygotic mutation in a pluripotent progenitor cell.…”
mentioning
confidence: 99%
“…The co‐occurrence of two different nevi or paired patches of mutant tissue that differ genetically from each other and from the background tissue is defined as “didymosis.” It would result from the presence of two different mutant alleles (at the same gene locus or at different loci) and a subsequent postzygotic recombination, which gives rise to two different homozygous daughter cells forming the skin lesions that are either allelic (originating from the same type of cell) or nonallelic (originating from different types of cell) . However, the concept of nonallelic didymosis has been recently questioned, as molecular research has shown that some skin disorders thought to be the result of such a genetic phenomenon may be caused by a single postzygotic mutation in a pluripotent progenitor cell being present in a heterozygous state (pseudodidymosis) …”
mentioning
confidence: 99%
“…Regarding our case, although we cannot exclude a random co‐occurrence of the two lesions, their close spatial arrangement might support a possible causal relationship. Based on the new concept of pseudodidymosis, it is possible to hypothesize that they could be due to a single postzygotic mutation in a pluripotent progenitor cell.…”
mentioning
confidence: 99%